VD_FINDINFO Jug / 2012 / 97 vom 3. April 2012 - VD Tribunal cantonal (2012)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE, PARTAGESENS GÉNÉRAL | 122 CC, 22 LFLP, 15 al. 2 LPP, 7 OLP, 12 OPP2